(3GdJLGQI GdEdcJQhfjIs - (3CejQ aQL(B, (3jhSas ((3GdEScfOQjI(B:s (3OGQ GdeWHhYGJ GdLGeYjI(B,s, 2008)
(3jVe GdJLGQI GdEdcJQhfjI, GdJYQja HbGfhf GdChfSjJQGd GdfehPLj HTCf GdJLGQI GdEdcJQhfI hOdjd JWHjb gPG GdbGfhf aj GdOhd GdeNJdaI, QSGFd GdHjGfGJ GdeYJQa HgG aj bGfhf GdJLGQI GdEcJQhfjI, GdJhbjY GdEdcJQhfj Ydi GdYbhO hGdeSJfOGJ GdEdcJQhfjI , OhQ GdJLGQh GdEdcJQhfjI aj eLGd fbd GdHVGFY heSJfOGJ fbd GdHVGFY, GSJNOGe KhQI GdeYdheGJ dUGdM GdSde hNjQ GdHTQjI, GdESJQGJjLjI GdYQHjI aj eLGd JcfhdhLjG GdeYdheGJs
(3GdeQGLY U(B.748s
Keywords: (3GdJLGQIs; (3GdJLGQI GdEdcJQhfjIs; (3GdJLGQI(B- (3JcfhdhLjG GdeYdheGJs